Analisis Perilaku Wajib Pajak Orang Pribadi Terhadap Pelaksanaan Self Assessment System: Suatu Studi di Bangkalan - Tarjo Tarjo; Indra Kusumawati (Jurnal Akuntansi dan Auditing Indonesia, 2006)
The objective of this study is to investigate the implementation of self assessment system. The data collected from 56 personal taxpayers in Bangkalan. The results indicate that self assessment system has not been implementation well. For example the taxpayer did not count tax return themselves. The taxpayers do not report because of their self awareness, rather because of the penalty.The tax officers has not been implemented the self assessment system well either, besides controlling function is conducted exaggeratedly. Although the service functions, in reality, taxpayers do not calculate their tax by themselves, but the tax officers do.Key words: taxpayers, fiskus, self assessment system.